Geronimo Stilton reporter. 1, Operation Shufongfong - Stilton, Geronimo (Stilton, Geronimo. Geronimo Stilton reporter, 2018)
The famous Prince Nogouda pays a visit to New Mouse City and ace reporter Geronimo Stilton has an exclusive interview. Meanwhile, at the Mouse Museum, the rare breed of Shufongfong lizards have been kidnapped! Could like Prince and his kingdom in the Bandel jungle have anything to do with this? Geronimo, Thea, Trap, and Benjamin are on the case!